Just for fun! How experimental spaces stimulate innovation in institutionalized fields. Issue 1 (January 2019) - Cartel, Mélodie; Boxenbaum, Eva; Aggeri, Franck
This paper examines the role of experimental spaces as a source of institutional innovation. We investigate the case of an experimental space that was instrumental in initiating the institutionalization of the European carbon market. Our findings highlight the key role of emotions in the simultaneous distancing from institutionalized patterns and engagement in an alternative action model. We subsequently develop a process model of how experimental spaces initiate institutional innovation in institutionalized fields. This model comprises three forms of institutional work. As previously established, boundary work consists in delineating the space from the field, hence mitigating external institutional pressures. We argue that two additional forms of institutional work are required when field conditions are unconducive to institutional innovation. Distancing work consists in designing rules and procedures that alleviate space members' deep-seated attachment to the field's dominant models. Anchoring work refers to the design of rules and procedures that connect the experimental space and the solution developed inside it to the field, hence facilitating its broader diffusion. We conclude with a discussion of how the design of experimental spaces and the deliberate use of emotions open new doors for generating institutional innovation.